Post-harvest losses: Global scale, solutions, and relevance to Ghana - Ridolfi, Carlotta; Hoffmann, Vivian; Baral, Siddhartha (International Food Policy Research Institute, 2018)
The post-harvest system comprises a range of interconnected activities, from the time of harvest through processing, marketing, preparation, and finally consumption decisions at the consumer level. Each year, large quantities of food are wasted or lost at each of these stages during their journey to consumers.